Modulating cellular deformability via 3D dextran hydrogel cultivation to regulate the microcirculation of mesenchymal stem cells in murine spleen and liver - Xiaolu Zhu; Zheng Wang; Yuanping Shi; Shuang Yao; Fengliang He; Xiuli Cong; Fang Teng (Experimental and Molecular Pathology, 2025)
For mesenchymal stem cell (MSC) therapy to be effective, the vascular system may be used to deliver and steer the cells to the target tissue. However, the expanded MSCs in petri dishes typically exhibit limited deformability and commonly excluded by the capillary networks when homing to the downstream organs via microcirculation. Here, we propose to utilize specially designed 3D dextran hydrogels and tuning the microscopic heterogeneity of hydrogel composition to make the administrated cells mechanically comply with the structure and mechanics of the capillary. The deformability of cells cultured in petri dishes, microcosmically homogeneous (HOM), and heterogeneous (HET) dextran hydrogels was investigated in vitro by measuring cell moduli through atomic force microscope (AFM), analyzing the expression of cytoskeletal protein via flow cytometry and fluorescent imaging. The in vitro experimental results demonstrate a progressive increase in cell deformability from 2D dishes, to HOM-hydrogel derived cells, and then to HET-hydrogel derived cells. The in vivo mouse experiment indicates the cells could deform accordingly and pass through easily with reduced resistance inside the mouse organs. It is suggested that the main destination of hMSC microcirculation could be selected between the spleen and liver of mice, by tuning cell mechanics that depends on the stimulus from HOM or HET hydrogel, which lays a potential foundation for the mechanically modified MSC therapy targeting organ lesions.